A noteworthy treatment of metastatic small‐cell lung cancer with afatinib, followed by subsequent development of rare metastatic lesions in the ascending and sigmoid colon. Issue 3 (12th March 2020) - Hsiao, Shih‐Chuan; Chen, Yi‐Hsien; Lo, Ching‐Chu; Lin, Ching‐I
Abstract: Background: Small‐cell lung cancer (SCLC) represents a group of highly fatal diseases with a tendency toward fast growth, early metastasis, and easy development of chemotherapy resistance. In the past 30 years, few advances have been made in the systemic treatment of SCLC, and cisplatin/etoposide has remained the standard of care for limited‐stage SCLC and, in combination with radiotherapy, extensive‐stage SCLC. The preferred metastatic sites of SCLC include the brain, liver, adrenal glands, bone, and bone marrow. However, bowel metastasis caused by SCLC is extremely rarely proved in patients while they are still alive (although autopsy studies suggest that silent metastases to the bowel are more common), and the standard treatment for bowel metastasis has never been reported. The mean time between the identification of gastrointestinal metastasis and mortality in patients with lung cancer is 100.6 days, with a range of 21–145 days. Case: We report the case of a patient with extensive SCLC (including brain metastasis), in which exon 19 deletion of epidermal growth factor receptor (EGFR) was detected. She initially refused chemotherapy and cranial radiotherapy and instead only agreed to oral target therapy. The second‐generation EGFR‐tyrosine kinase inhibitor (TKI), afatinib, was administered to the patient, and partial remission, including smaller metastatic brain tumors, was noted. Even though the subsequent development of rare metastatic lesions in the ascending and sigmoid colon was proved by colonoscopic biopsies, the prolonged overall survival (400 days) without standard treatment was marked in this case. Conclusion: The patient with extensive metastasis of SCLC did not receive standard systemic chemotherapy. Instead, she initially received second‐generation EGFR‐TKI afatinib alone and later on whole brain radiotherapy as well (3 weeks before she expired). The prolonged overall survival of 400 days was marked and is worthy of sharing and further investigation.